Patterns of IgE sensitization in house dust mite‐allergic patients: implications for allergen immunotherapy. Issue 2 (13th November 2015) - Batard, T.; Baron‐Bodo, V.; Martelet, A.; Le Mignon, M.; Lemoine, P.; Jain, K.; Mariano, S.; Horiot, S.; Chabre, H.; Harwanegg, C.; Marquette, C. A.; Corgier, B. P.; et al.
Abstract: Background: Understanding patterns of IgE sensitization in Dermatophagoides ‐allergic patients living in various geographical areas is necessary to design a product suitable for worldwide allergen immunotherapy (AIT). Methods: Using a HIFI Allergy customized microarray assay, IgEs specific for 12 purified allergens from Dermatophagoides pteronyssinus or D. farinae were assessed in sera from 1302 house dust mite (HDM)‐allergic patients living in various areas. Comprehensive mass spectrometric (MS) analyses were conducted to characterize HDM extracts, as well as purified bodies and feces. Results: Patterns of IgE reactivity to HDM allergens are comparable in all cohorts of patients analyzed, encompassing adults and 5‐ to 17‐year‐old children, as well as American, Canadian, European, and Japanese patients. Overall, >70% and >80% of HDM‐allergic patients are sensitized to group 1 and group 2 allergens, respectively, from D. pteronyssinus and/or D. farinae species. Furthermore, 20–47% of patients also have IgEs to allergens from groups 4, 5, 7, 13, 15, 21, and 23. All patients have IgEs to allergens present in mite bodies and feces. MS‐based analyses confirmed the presence of mite allergens recorded by IUIS in D. pteronyssinus and D. farinae extracts, with groups 2, 8, 10, 11, 14, and 20 prominent in bodies and groups 1, 6, 18, and 23 well represented in feces. Conclusions: Mite‐specific AIT should rely upon a mixture of D. pteronyssinus and D. farinae extracts, manufactured from both feces and bodies. Such a combination is appropriate to treat children and adult Dermatophagoides ‐allergic patients from Asia, Europe, and North America.